On the Computations of Gas-Solid Mixture Two-Phase Flow (Advances in Applied Mathematics and Mechanics, 2014)
This paper presents high-resolution computations of a two-phase gas-solid mixtureusing a well-defined mathematical model. The HLL Riemann solver is applied tosolve the Riemann problem for the model equations. This solution is then employedin the construction of upwind Godunov methods to solve the generalinitial-boundary value problem for the two-phase gas-solid mixture. Severalrepresentative test cases have been carried out and numerical solutions areprovided in comparison with existing numerical results. To demonstrate therobustness, effectiveness and capability of these methods, the model resultsare compared with reference solutions. In addition to that, these results arecompared with the results of other simulations carried out for the same set oftest cases using other numerical methods available in the literature. The diversecomparisons demonstrate that both the model equations and the numerical methodsare clear in mathematical and physical concepts for two-phase fluid flow problems.